Pelatihan Penulisan Karya Tulis sebagai Upaya Menumbuhkan Rasa Percaya Diri dan Kreativitas Siswa Sekolah Dasar - Mubarok, Tyas Alhim; Arini, Fitri; Utami, Nurcholisa Rizqi (Subservire: Jurnal Pengabdian Masyarakat, 2024)
Writing is one of the language skills. Every student will be taught how to write from an early age. Writing skills are very important for students to support their learning process. In addition, writing has many benefits including improving memory function, reducing stress, and providing a greater feeling of happiness. This community service activity aims to train students at MI Aisyiyah Kertosono to write a simple written work. This activity is intended for students in grades 4, 5, and 6. The implementation method includes 1) providing material by way of presentation, 2) questions and answers, 3) writing exercises with a specified theme, 4) writing exercises with a free theme, 5) presenting the results of the written work. In addition to training students' writing skills, this activity is also expected to foster students' self-confidence in pouring stories into written form. The results of the activity produce written works that are published and printed for the library collection. In addition, this activity can foster students' self-confidence and creativity in pouring their ideas into written form.